2016
DOI: 10.2147/idr.s117886
|View full text |Cite
|
Sign up to set email alerts
|

Probiotics improve the efficacy of standard triple therapy in the eradication of <em>Helicobacter pylori</em>: a meta-analysis

Abstract: IntroductionHelicobacter pylori colonization is present in half of the world’s population and can lead to numerous gastrointestinal diseases if left untreated, including peptic ulcer disease and gastric cancer. Although concurrent triple therapy remains the recommended treatment regimen for H. pylori eradication, its success rate and efficacy have been declining. Recent studies have shown that the addition of probiotics can significantly increase eradication rates by up to 50%. This meta-analysis examines the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
44
1
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(51 citation statements)
references
References 55 publications
(47 reference statements)
0
44
1
2
Order By: Relevance
“…All the 6 identified studies showed a reduction in diarrhoea with probiotic consumption vs placebo. This is supported by the results of 2 recent meta‐analyses that each examined the effects of a variety of probiotics on H. pylori eradication rates (primary endpoint) and diarrhoea associated with H. pylori eradication therapy (secondary endpoint) . The first, a meta‐analysis of 13 studies (1 of which is included in the current review) involving a total of 2306 patients, found a reduced risk of diarrhoea in the probiotic group compared with the placebo group (risk ratio [RR]: 0.51; 95% confidence interval [CI]: 0.31‐0.84; P = 0.008) .…”
Section: Discussionmentioning
confidence: 63%
See 1 more Smart Citation
“…All the 6 identified studies showed a reduction in diarrhoea with probiotic consumption vs placebo. This is supported by the results of 2 recent meta‐analyses that each examined the effects of a variety of probiotics on H. pylori eradication rates (primary endpoint) and diarrhoea associated with H. pylori eradication therapy (secondary endpoint) . The first, a meta‐analysis of 13 studies (1 of which is included in the current review) involving a total of 2306 patients, found a reduced risk of diarrhoea in the probiotic group compared with the placebo group (risk ratio [RR]: 0.51; 95% confidence interval [CI]: 0.31‐0.84; P = 0.008) .…”
Section: Discussionmentioning
confidence: 63%
“…Similarly, the second meta‐analysis, which involved 4515 patients from 30 RCTs (5 of which are included in this systematic review), found a significant reduction in the risk of diarrhoea with the addition of probiotics to standard triple therapy compared with triple therapy alone (RR: 0.549; 95% CI: 0.391‐0.771; P = 0.001). The addition of probiotics to standard triple therapy also significantly increased H. pylori eradication rates compared with triple therapy alone ( P < 0.001) …”
Section: Discussionmentioning
confidence: 99%
“…A separate meta‐analysis which emphasized the heterogeneity of the 13 studies identified that pooled relative risk of eradication was significantly higher in the probiotic supplementation group than in the control group and the incidence of total antibiotic‐related side effects was lower in the probiotic supplementation group than in the control group . A further meta‐analysis of 30 randomized clinical trials with significant heterogeneity found eradication rates improved by 12.2% when probiotics were used in supplementation …”
Section: Probioticsmentioning
confidence: 99%
“…Lactobacillus , Saccharomyces , Bifidobacterium and other probiotic compounds seem to be beneficial to H. pylori eradication therapy in meta‐analyses . It is difficult ot conclude which probiotic is the best for H. pylori eradication therapy based on the currently available literatures.…”
Section: Further Factors That Need To Be Consideredmentioning
confidence: 99%
“…Moreover, variations in the ethnicity of the participants, the methods of administering probiotics and local antibiotic resistance may also have greatly influenced the results. Additionally, several metaanalyses 29,[40][41][42][43][44][45][46][47][48][49][50] have been published during the past decade covering various probiotics used in H. pylori eradication, analyzing their roles in H. pylori eradication and therapy-related adverse events such as diarrhea, nausea, dyspepsia and dysgeusia. Most of these studies have claimed that patients can benefit from supplementation with probiotics in H. pylori eradication therapy.…”
Section: Probiotics and H Pylori Eradication Therapymentioning
confidence: 99%